Pengaruh Terpaan Berita Perkosaan di Tribunnews.com Terhadap Sikap Waspada Mahasiswi - Rika Anistania (Journal of Communication Sciences (JCoS), 2020)
This study is to determine the effect between the news of rape of UGM students on Tribunnews.com on the alert attitude of female students in interacting and how much influence it has. This research uses associative quantitative survey method. The population and sample of this study were 36 students of KKN Period II 2018/2019 University of Muhammadiyah Malang. The data collection techniques used questionnaires and documentation. Test the research instrument using the validity test and reliability test. The data analysis technique used simple linear regression and t test. The value of R square (coefficient of determination) = 0.130 and the value of R (coefficient of correlation) = 0.361. This value indicates the relationship between variable X and variable Y is included in the weak category. The value of t table (α = 0.05; residual df = 34) is 1.690. It is known that t count> t table is 2.255> 1.690 or the sig t value (0.031) <α = 0.05, so the effect of variable X on variable Y is significant. From this analysis, it can be concluded that 13% of the Y variable is influenced by the X variable. Meanwhile, 87% of the Y variable is influenced by other variables.